Islas de calor urbano mediante imágenes satelitales en la ciudad de Juliaca durante el año 2019 - Sucapuca Mamani, Reyder Orlando (2022)
This research was carried out in the city of Juliaca between April and September 2019, with the objective of identifying urban heat islands through surface temperature maps based on satellite images of the TIRS thermal sensor. Surface emissivity corrections were used where the surface temperature was estimated and urban heat islands were identified in the city. The results show eight urban heat islands; located in the Public Welfare Society (24.8 °C), Cerro Huayna Roque (28.3 °C), Plaza Vea Shopping Center (25.6 °C), Francisco Bolognesi Barracks (26 °C), Estadio San Isidro (25.3 °C), Parque Cholo (24.4 °C), Estadio Politécnico de los Andes (26.1 °C) and the Manuel A. Odría stadium (25.9 °C). It is concluded that urban heat islands occur in the center of the city and also in places with bare soil.